Creation of a model to predict survival in patients with refractory coeliac disease using a multinational registry. Issue 7 (3rd August 2016) - Rubio‐Tapia, A.; Malamut, G.; Verbeek, W. H. M.; van Wanrooij, R. L. J.; Leffler, D. A.; Niveloni, S. I.; Arguelles‐Grande, C.; Lahr, B. D.; Zinsmeister, A. R.; Murray, J. A.; Kelly, C. P.; Bai, J. C.; et al.
Summary: Background: Refractory coeliac disease is a severe complication of coeliac disease with heterogeneous outcome. Aim: To create a prognostic model to estimate survival of patients with refractory coeliac disease. Methods: We evaluated predictors of 5‐year mortality using Cox proportional hazards regression on subjects from a multinational registry. Bootstrap resampling was used to internally validate the individual factors and overall model performance. The mean of the estimated regression coefficients from 400 bootstrap models was used to derive a risk score for 5‐year mortality. Results: The multinational cohort was composed of 232 patients diagnosed with refractory coeliac disease across seven centres (range of 11–63 cases per centre). The median age was 53 years and 150 (64%) were women. A total of 51 subjects died during a 5‐year follow‐up (cumulative 5‐year all‐cause mortality = 30%). From a multiple variable Cox proportional hazards model, the following variables were significantly associated with 5‐year mortality: age at refractory coeliac disease diagnosis (per 20 year increase, hazard ratio = 2.21; 95% confidence interval, CI: 1.38–3.55), abnormal intraepithelial lymphocytes (hazard ratio = 2.85; 95% CI: 1.22–6.62), and albumin (per 0.5 unit increase, hazard ratio = 0.72; 95% CI: 0.61–0.85). A simple weighted three‐factor risk score was created to estimate 5‐year survival. Conclusions: Using data from a multinational registry and previously reported risk factors, we create a prognostic model to predict 5‐year mortality among patients with refractory coeliac disease. This new model may help clinicians to guide treatment and follow‐up.